PERANCANGAN SISTEM PERAMALAN CUACA BERBASIS LOGIKA FUZZY DI KOTA BATAM - NAPITUPULU, RIKKI LEONARDO; Handoko, Koko (LPPM Universitas Putera Batam, 2022)
Weather is also an important factor in supporting human activities, especially in Indonesia. Human activities that are highly dependent on weather conditions include flight activities, shipping, land travel, agriculture, companies that use the sun as a dryer for their production materials, daily activities (drying cloth). Every day, BMKG Indonesia as an institution engaged in Meteorology, Climatology, Air Quality and Geophysics is tasked with providing information on weather forecasts in Indonesia based on available data. However, at this time it is very difficult to predict the weather conditions because of rapidly changing climate conditions resulting in irregular season changes. Weather conditions are influenced by interrelated elements, namely temperature, humidity, air pressure and the intensity of sunlight. Erratic weather changes can only occur for a few hours and differ in various regions (Puspita, 2016). Fuzzy logic is a level of Boolean logic that deals with the concept of partial truth. Where fuzzy logic maps an input space into an output space by using IF- THEN rules. With the help of the application of Fuzzy logic, this research has the aim of processing the data obtained from temperature, air, and air pressure using Sugeno's fuzzy logic and testing accuracy using MATLAB.